2009
DOI: 10.1186/1471-2105-10-169
|View full text |Cite
|
Sign up to set email alerts
|

A core-attachment based method to detect protein complexes in PPI networks

Abstract: Background: How to detect protein complexes is an important and challenging task in post genomic era. As the increasing amount of protein-protein interaction (PPI) data are available, we are able to identify protein complexes from PPI networks. However, most of current studies detect protein complexes based solely on the observation that dense regions in PPI networks may correspond to protein complexes, but fail to consider the inherent organization within protein complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
329
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 338 publications
(341 citation statements)
references
References 54 publications
0
329
0
Order By: Relevance
“…This is because practically all methods find it difficult to detect small complexes (consisting of fewer than four proteins) and hence explicitly exclude these complexes from their predictions (e.g. see [55]). Besides, the possibility of a predicted complex matching a reference complex that is small purely by chance is relatively high [61], and therefore evaluating the methods becomes challenging (further discussed in Section 2.4.3).…”
Section: Comparative Assessment Of Complex Detection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because practically all methods find it difficult to detect small complexes (consisting of fewer than four proteins) and hence explicitly exclude these complexes from their predictions (e.g. see [55]). Besides, the possibility of a predicted complex matching a reference complex that is small purely by chance is relatively high [61], and therefore evaluating the methods becomes challenging (further discussed in Section 2.4.3).…”
Section: Comparative Assessment Of Complex Detection Methodsmentioning
confidence: 99%
“…CORE [54], COACH [55], MCL-CAw [56,57] and CACHET [58] look for clusters that adhere to the core-attachment organization, noted originally in yeast complexes by Gavin et al [6]. Large-scale pull-down of yeast complexes using TAP-MS in [6] revealed that proteins within complexes are organized as two distinct sets: cores that constitute central functional units of complexes, and attachments that aid core proteins in their functions.…”
Section: Methods Incorporating Core-attachment Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Gavin et al proposed that a protein complex consists of high-density core proteins and some attachment proteins. Several complex detection algorithms have been developed based on this notion [13][14][15].…”
Section: Introductionmentioning
confidence: 99%